Comparison of Thyroid Dysfunction in Patients with Controlled Versus Uncontrolled Diabetes Mellitus: A Comparative Cross-Sectional Study: Thyroid Dysfunction with Controlled Versus Uncontrolled Diabetes Mellitus - Qamar, Khansa; Ansari, Masud Ali; Tofique, Mahneem; Naeem, Jannat; Shams, Sara; Fatima, Fizza (Pakistan Journal of Health Sciences, 2025)
Thyroid dysfunction (TD) and type 2 diabetes mellitus (DM) are the two endocrine conditions most frequently encountered in clinical settings. Objectives: To compare the frequency of thyroid dysfunction in patients with controlled versus uncontrolled DM. Methods: This comparative cross-sectional study was conducted at the Pathology Department of Nishtar Hospital, Multan, from February to July 2025. Diabetic patients aged 30–70 years of both genders were enrolled in the study as uncontrolled diabetes (n=124) and controlled diabetes (n=124). Patients with pre-existing TD, on its treatment, or using medications known to alter thyroid function were excluded. Demographic details, including age, gender, duration of diabetes, and hypertension status, were recorded. TD was categorized into subclinical hypothyroidism, clinical hypothyroidism, subclinical hyperthyroidism, and hyperthyroidism. Descriptive statistics were run through SPSS version 23.0, and the Shapiro-Wilk test for normality. Chi-square test at 5% significance level was used for comparisons, with stratification done to control confounding. Results: Among 248 participants, the mean age was 49.2 ± 10.3 years. Males constituted 48% and 73.4% had hypertension. TD was found in 14.5% of diabetics, more common in uncontrolled (69.4%) than controlled diabetes (30.6%) (p=0.012). Most frequent type was subclinical hypothyroidism (6%), followed by hypo- and hyperthyroidism (3.2% each), and subclinical hyperthyroidism (2%). TD was high in uncontrolled diabetics ≥50 years, females, and hypertensive patients. Conclusions: Thyroid dysfunction was remarkably more common in persons with uncontrolled diabetes, particularly in older age, females, and hypertensives.